A case of cholecystitis considered as a polyp of the gallbladder on diagnostic imaging - MIYAKE, Kazuhiko; SAITO, Keiichi; TAKIKAWA, Hajime; KINJO, Kazuo; YOKOTE, Mikihiro; YOKOTE, Michiko; NISHIKAWA, Kou; YAMANAKA, Masami; KITAZAKI, Kyoichiro (Tando, 1993)
We reported a case of cholecystitis which was considered as a polyp of the gallbladder on diagnostic imaging, with the review of a literature. A 65-year-old male was admitted to our hospital because of the right upper abdominal pain. Ultrasonography showed a papillary polypoid lesion at the body of the gallbladder as well as whole wall thickening of the gallbladder. The polyp was maximum 35 mm in diameter and did not change in the shape after the therapy for cholecystitits, highly suspectious for a cancer. Histological examination of the surgical specimen revealed cholecystitis with granuloma and cholesterosis without any evidence of malignancy.